Vibration reduction of FG-CNTR piezoelectric laminated composite cantilever plate under aerodynamic load using full-dimensional state observer. (15th March 2022) - Lu, S.F.; Li, H.J.; Zhang, W.; Song, X.J.
Highlights: Control method is proposed to suppress the vibration of cantilever plate. Effective material properties are obtained using the rule of mixtures. Governing equations of motion for FG-CNTR laminated composite plat are established. Piezoelectric patches are used as actuators and sensors. Full-dimensional state observer is introduced to design the robust controller. Abstract: A robust control method is developed to suppress the vibrations of the functionally graded carbon nanotube-reinforced (FG-CNTR) piezoelectric laminated composite cantilever plate subjected to the aerodynamic force and thermal environment. The distributions of the carbon nanotubes (CNTs) in the entire plate thickness are classified as the functionally graded (FG) or uniform distributions (UD). The effective material properties are obtained using the rule of mixtures. The classic laminated composite plate theory and Hamilton principle are used to establish the governing equations of motion for the FG-CNTR laminated composite cantilever plate under combined the aerodynamic force and thermal environment. Galerkin method is used to obtain a two-degree-of-freedom ordinary differential control equation. To actively suppress the vibration, the piezoelectric patches are used as the actuators and sensors which are attached to the upper and lower surfaces of the FG-CNTR laminated composite cantilever plate. A full-dimensional state observer is introduced to design the robust controller. To verify the efficiency of the control strategy, a comparison between the robust controller and velocity feedback controller (VFC) indicates that the robust controller has better control efficiency than the VFC. The effects of the CNT distribution, CNT volume fraction, temperature and aspect ratio on the dynamic behaviors of the laminated composite plates are studied. The effectiveness and accuracy of the proposed robust controller are verified through numerical simulations under different cases.